Review of the Indian species of the genus Eurymeros Bhat (Braconidae: Alysiinae) with some nomenclatural changes - Gupta, Ankita; van Achterberg, Cornelis (Zootaxa, 2022)
The genus Eurymeros Bhat (Braconidae, Alysiinae) is reviewed from India and three species E. gibbosa Sharma 1983, E. mangifera Sharma 1983, and E. namkumensis Sharma & Naqvi 1993, are transferred to the genus Euscelinus Westwood 1882 (comb. nov.; Braconidae, Doryctinae) and synonymized with the type species (Euscelinus sarawacus Westwood 1882; syn. nov.). The type species and only known species E. tumespiraculum Bhat is redescribed.